(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Induction and augmentation are common obstetric interventions used to manage labor, yet their comparative impact on post-delivery outcomes and maternal psychological well-being remains variably reported. Understanding these differences is critical for informed decision-making, patient-centered care, and optimizing both physical and mental health outcomes for mothers. Objective: To compare induction and augmentation of labor in terms of maternal postpartum outcomes and psychological behavior, with emphasis on pain perception, anxiety, mood, breastfeeding initiation, postpartum recovery, and perceived control during the birth experience. Methods: A prospective cohort study (specify as appropriate) was conducted at a tertiary care hospital in Peshawar 1st January 2025 to 30th June 2025. Eligible participants included women delivering singleton or multiple pregnancies at term who underwent labor induction or labor augmentation. Key variables collected included mode of labor management (induction vs augmentation), mode of delivery, hospital registration number and age. Psychological assessments were administered postpartum utilizing the Kessler psychological distress scale (k10). Statistical analysis compared both groups using SPSS version 23.0 using the chi-square test as indicated while keeping p-value at less than 0.05 as statistically significant. Results: In adjusted analyses, induction vs augmentation was associated with differences in psychological outcomes such as indicated by the KPDS scores. A t-value of 4.06 with p < 0.001 means there is strong evidence that the mean duration of labor differs between women who had IOL and those whose labor was Augmented. In plain terms, the type of procedure (IOL vs Augmented) does not show a significant association with whether the delivery was a C-section or NVD in this dataset. Although women induced with IOL appeared to have slightly more C-sections than those with augmented labor, the difference was not statistically significant (χ² = 2.34, p = 0.126). This means the procedure type was not strongly related to delivery mode in this sample of 100 cases. Conclusions: Both induction and augmentation of labour influence post-delivery physical and psychological outcomes, but their effects are nuanced and mediated by factors such as indication, cervical favorability, and care practices. Clinicians should tailor management to individual risk profiles, communicate clearly about expectations and potential psychological impacts, and provide targeted support to enhance maternal well-being and satisfaction after birth.